Influencia de la relación agua/cemento y tipos de curado sobre la compresión, densidad, ataque de cloruros y sulfatos de un concreto estructural - Ortecho Castillo, Ronald Alex (2023)
At present, it is well known that concrete is the most used material worldwide for the development of new infrastructures, as well as in our country, the growth of the construction sector is a latent reality; however, the growth shows large rates in the increase of self-construction of an informal nature, where the quality of the process of preparing and curing the concrete is questioned, it is common to see that the proper design is not respected according to the use of the structure , there is an erroneous tendency to apply more water to make the mixture more workable, in addition to not providing curing after the structures are poured. In the present investigation, the water/cement ratio and the type of curing were evaluated on compressive strength (NTP 339.034), density (ASTM C 642) and resistance to attack by chlorides (NT BUILD 492) and sulfates (E0. 60) in a conventional concrete mix for structural design use 210 kg/cm2 made with Pacasmayo Type Ico cement; concrete w/c ratios of 0.54, 0.56, 0.58, 0.60 and 0.62 were used and 3 types of curing were used with Chema Membranil Vista curing additive, conventional curing used on site and theoretical curing - laboratory regulations. The main objective of the study is that, based on the investigation, the influence of using an adequate water/cement ratio for structural design is verified, in addition to verifying the effectiveness of the type of curing used in a conventional way when contrasting it with the theoretical curing of the laboratory. For the concrete tests in the hardened state, cylindrical specimens of 100 mm x 200 mm were made, evaluated at 28 days in the various types of curing mentioned above; and for resistance to chlorides and sulfates, they were made from cross sections to additional cylindrical specimens with the same designs. In the compressive strength test, the results decreased as the water/cement ratio increased, up to 45%; For the samples made with a ratio of 0.54, a resistance of 294 kg/cm2 was obtained with curing in the laboratory, even exceeding the reference value of 210 kg/cm2 . In the density test, values from 2.35g/cm3 to 2.51g/cm3 were obtained, cured on site and at the laboratory level, respectively. Likewise, the resistance to attack by chlorides and sulfates showed that the optimal w/c ratio was 0.54 with a theoretical curing in the laboratory, obtaining values of 0.52 g and 8.60x10-12 m2 /s.